2002
DOI: 10.1046/j.1365-2168.2002.02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the penis

Abstract: Penile fracture is not rare. Radiological investigations are expensive and may delay treatment. Current management favours early surgical exploration to prevent complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
298
1
22

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(330 citation statements)
references
References 96 publications
9
298
1
22
Order By: Relevance
“…Sexual intercourse was found to be the most important cause in western countries. 4 Those from the Middle East resulted mainly from penile manipulation; in a series of 373 patients, Zargooshi 19 indicated that the most common mechanism of fracture penis was acute bending of the erect penis in an attempt to achieve detumescence (76.4%). In our series, sexual intercourse was the main cause of trauma, similar to that reported in western countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual intercourse was found to be the most important cause in western countries. 4 Those from the Middle East resulted mainly from penile manipulation; in a series of 373 patients, Zargooshi 19 indicated that the most common mechanism of fracture penis was acute bending of the erect penis in an attempt to achieve detumescence (76.4%). In our series, sexual intercourse was the main cause of trauma, similar to that reported in western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies favor early surgical repair because of the adequate functional and cosmetic results with minimal complications. [2][3][4][5][6][7][8][9][10] Late complications of penile fracture comprise ED, deviation of the erect penis, development of plaques resembling those of La Peyronie disease, urethrocavernous or urethrocutaneous fistula and poor urinary stream. [9][10][11][12] ED is a critical problem that may have serious physical and psychological consequences.…”
Section: Introductionmentioning
confidence: 99%
“…During erection, the tunica albuginea thins down to between 2 mm and 0.25-0.5 mm, and as a result of the trauma, rupture of the tunica albuginea occurs when the intracavernous pressure exceeds 1500 mm Hg. 4,18 Generally, only one corpus cavernosum is affected but both the corpora and urethra may be involved. In all of our cases, the tunical tears were unilaterally (16 right, 14 left).…”
Section: Discussionmentioning
confidence: 99%
“…2,3 The best initial management of penile fracture is usually immediate surgical repair. [4][5][6] Immediate surgical intervention with evacuation of hematoma and repair of the ruptured tunica albuginea shows good functional results with low morbidity and short hospital stay. In earlier studies, a conservative regimen such as ice pack compresses followed by hot packs, foley catheterization or suprapubic urinary diversion, compression bandages, erectioninhibiting estrogens, antibiotics, and anti-inflammatory medicines were recommended.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation